Substrate Specificity of Barley Cysteine Endoproteases EP-A and EP-B - Davy, Anne (American Society of Plant Physiologists, 1998)
The cysteine endoproteases (EP)-A and EP-B were purified from green barley (Hordeum vulgare L.) malt, and their identity was confirmed by N-terminal amino acid sequencing. EP-B cleavage sites in recombinant type-C hordein were determined by N-terminal amino acid sequencing of the cleavage products, and were used to design internally quenched, fluorogenic peptide substrates. Tetrapeptide substrates of the general formula 2-aminobenzoyl-P(2)-P(1)-P(1)′-P(2)′-tyrosine(NO(2))-aspartic acid, in which cleavage occurs between P(1) and P(1)′, showed that the cysteine EPs preferred phenylalanine, leucine, or valine at P(2). Arginine was preferred to glutamine at P(1), whereas proline at P(2), P(1), or P(1)′ greatly reduced substrate kinetic specificity. Enzyme cleavage of C hordein was mainly determined by the primary sequence at the cleavage site, because elongation of substrates, based on the C hordein sequence, did not make them more suitable substrates. Site-directed mutagenesis of C hordein, in which serine or proline replaced leucine, destroyed primary cleavage sites. EP-A and EP-B were both more active than papain, mostly because of their much lower K(m) values.